The Importance of Civic Education and Democracy in Free Textbooks in Mexico, 1959-2018 - Inclán Oseguera, Silvia; León Rojo, Marco Antonio (Revista Mexicana de Ciencias Políticas y Sociales, 2021)
This article explores Mexico's education policy since 1959 with the aim of observing the relative importance of civic education and analyzing the democratic content of the free official textbooks under the following thematic categories: democracy, conflict, limited authority, and citizen responsibility. The analysis finds low relative importance and scarce democratic contents up until 2009-2012, an emphasis on developing abilities and the inclusion of ethical principles with little articulation and vision as well as lack of exercises and practice since 2012.